2018
DOI: 10.1016/j.amjcard.2017.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of and Prognostic Significance of Cardiac Involvement at Presentation in Hereditary Transthyretin-Derived Amyloidosis and the Value of N-Terminal Pro-B-Type Natriuretic Peptide

Abstract: The aim of this study is to assess the prevalence of cardiac involvement in hereditary transthyretin-derived (ATTRm) amyloidosis at the time of diagnosis and to determine the diagnostic and clinical value of N-terminal pro-B-type natriuretic peptide (NT-proBNP). The University Medical Center Groningen is the national center of expertise for amyloidosis. All consecutive patients between 1994 and 2016 with ATTRm amyloidosis were followed prospectively. Baseline was set at the time of the first positive biopsy. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 27 publications
1
25
0
2
Order By: Relevance
“…Echocardiography and cardiac MRI typically show myocardial thickening, including the interatrial septum. 13 TTR-CA is the major cause of death in patients with 1 In a study of 263 patients with TTR-CA, cardiac MRI revealed asymmetric hypertrophy associated with hypertrophic cardiomyopathy as the commonest pattern of ventricular remodeling in ATTR-CA.…”
Section: Cardiac Involvement In Attrm Amyloidosis (Ttr-ca)mentioning
confidence: 99%
See 2 more Smart Citations
“…Echocardiography and cardiac MRI typically show myocardial thickening, including the interatrial septum. 13 TTR-CA is the major cause of death in patients with 1 In a study of 263 patients with TTR-CA, cardiac MRI revealed asymmetric hypertrophy associated with hypertrophic cardiomyopathy as the commonest pattern of ventricular remodeling in ATTR-CA.…”
Section: Cardiac Involvement In Attrm Amyloidosis (Ttr-ca)mentioning
confidence: 99%
“…8 TTR-CA is already present at the time of the first positive biopsy in 51% of the patients. 13 TTR-CA most frequently manifests clinically as heart failure with normal systolic function, conduction blocks, ventricular arrhythmias, or sudden cardiac death (SCD). 14…”
Section: Cardiac Involvement In Attrm Amyloidosis (Ttr-ca)mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Mutant ATTR was once believed to be a rare autosomal dominant disease, restricted to an endemic presence in specific areas; however, with the progression of molecular and biochemical analyses, it has become clear that this disease occurs worldwide. [8][9][10][11] Because TTR-derived amyloid fibril deposition causes peripheral and autonomic polyneuropathy, it is reasonable to speculate that the cardiac neuronal homeostasis is altered in patients with ATTRm amyloidosis. 4 To date, over 140 TTR mutations have been identified, 5 with ATTRm amyloidosis symptoms varying according to the TTR mutation.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] In particular, cardiac involvement causes heart failure and cardiac arrhythmias due to infiltrative and restrictive cardiomyopathy and impacts the prognosis of patients with ATTR. [8][9][10][11] Because TTR-derived amyloid fibril deposition causes peripheral and autonomic polyneuropathy, it is reasonable to speculate that the cardiac neuronal homeostasis is altered in patients with ATTRm amyloidosis. A reduced heart-to-mediastinum uptake (HM) ratio on 123-iodine metaiodobenzylguanidine ( 123 I-MIBG) imaging, which is a noninvasive tool for assessing cardiac sympathetic nerve activity, has been reported to predict a poor prognosis in patients with ATTRm amyloidosis.…”
Section: Introductionmentioning
confidence: 99%